Mucosal-associated invariant T cells in Giant Cell Arteritis. Issue 121 (July 2021) - Ghesquière, Thibault; Ciudad, Marion; Ramon, André; Greigert, Hélène; Gerard, Claire; Cladière, Claudie; Thébault, Marine; Genet, Coraline; Devilliers, Hervé; Maurier, François; Ornetti, Paul; Quipourt, Valérie; et al.
Abstract: This study aimed to assess the implication of mucosal-associated invariant T (MAIT) cells in GCA. Blood samples were obtained from 34 GCA patients (before and after 3 months of treatment with glucocorticoids (GC) alone) and compared with 20 controls aged >50 years. MAIT cells, defined by a CD3 + CD4 − TCRγδ - TCRVα7.2 + CD161 + phenotype, were analyzed by flow cytometry. After sorting, we assessed the ability of MAIT cells to proliferate and produce cytokines after stimulation with anti CD3/CD28 microbeads or IL-12 and IL-18. MAIT were stained in temporal artery biopsies (TAB) by confocal microscopy. MAIT cells were found in the arterial wall of positive TABs but was absent in negative TAB. MAIT frequency among total αβ-T cells was similar in the blood of patients and controls (0.52 vs. 0.57%; P = 0.43) and not modified after GC treatment (P = 0.82). Expression of IFN-γ was increased in MAIT cells from GCA patients compared to controls (44.49 vs. 32.9%; P = 0.029), and not modified after 3 months of GC therapy (P = 0.82). When they were stimulated with IL-12 and IL-18, MAIT from GCA patients produced very high levels of IFN-γ and displayed a stronger proliferation compared with MAIT from controls (proliferation index 3.39 vs. 1.4; P = 0.032). In GCA, the functional characteristics of MAIT cells are modified toward a pro-inflammatory phenotype and a stronger proliferation capability in response to IL-12 and IL-18, suggesting that MAIT might play a role in GCA pathogenesis. Our results support the use of treatments targeting IL-12/IL-18 to inhibit the IFN-γ pathway in GCA. Highlights: MAIT cells are present in lesions of Giant Cell Arteritis (GCA). Their functional characteristics are modified toward a pro-inflammatory phenotype. They display a stronger proliferation capability in response to IL-12 and IL-18 and produce higher level of IFN-γ.